Modelling of the degradation of martensitic stainless steels by the Boudouard reaction. (15th August 2020) - Gong, Y.; Young, D.J.; Atkinson, C.; Olszewski, T.; Quadakkers, W.J.; Reed, R.C.
Graphical abstract: Highlights: Simultaneous oxidation and carburisation are studied for P92 and VM12 steels exposed to CO 2 gas at 550 ° C. Physically based modeling accounting for the carbon diffusion and the sluggish Boudouard reaction are developed. Moisture decreases the rate of Boudouard reaction, with its effect more significant for the VM12 alloy than for P92. Unexpectedly high effective diffusion coefficient of carbon in the substrate is found. Abstract: Numerical modelling of the degradation of P92 and VM12 martensitic stainless steels in gaseous (i) 70% CO 2 -30%H 2 O and (ii) Ar-50%CO 2 at 550 ° C is reported, emphasising the formation of duplex oxide scale and internal carburisation. A 1D numerical model is presented for the evolution of multiphase regions, subject to a Robin-type boundary condition representing a Boudouard surface reaction. The surface reaction kinetics at the spinel/substrate interface and the carbon transport kinetics in the substrate result in unusual carbon concentration profiles, measured here by glow-discharge optical emission spectroscopy (GDOES). Analysis of experimental data indicates that moisture decreases the rate of the surface reaction, despite higher carbon activity of the gas.